Management of odontogenic infections in the context of COVID-19 - Concha-Cusihuallpa, Hiroshi (2022)
Odontogenic infections are a group of pathologies that can be life threatening, during the pandemic with the temporary closure of public and private dental practices after the onset of COVID-19 there was an increase in care needs with a great possibility of congesting the health services, this condition increased morbidity and mortality caused by other more prevalent diseases. According to some reports shown in the literature at the beginning of the pandemic, there was a reduction in patients with cervicofacial infection of dental etiology, this may be due to the mandatory confinement of the patient by government guidelines. Successful management of odontogenic infections depends on successful classification of severity in primary care and timely emergency treatment provided by dental care centers with all their available resources. The rational management of an odontogenic infection involves an early diagnosis with the appropriate complementary tests that allow determining the extension of the process and the simultaneous application of the therapeutic trinomial between early empirical antibiotic coverage, defocusing, incision and drainage, this scheme will be especially important for success in the treatment.